Developing and using expressed sequence tags to study the predatory mite Phytoseiulus persimilis Athias-Henriot (Paraistiformes, Mesostigmata, Phytoseiidae) - Weng Huang, Ju Lin (Kansas State University, 2011)
The predatory mite Phytoseiulus persimilis (Acari, Phytoseiidae) is one of the most frequently released natural enemies for biological control of spider mites in greenhouse and outdoors crops. In this research, I utilized Expresses Sequence Tags (ESTs), the most cost effective approach for transcriptome exploration, to study three different aspects of this arachnid species for which there is little genomic information. I combined two EST datasets from different whole body cDNA libraries and analyzed by bioinformatics means. Approximately 54% of 10,256 uniESTs were annotated based on the homology to sequences in the National Center for Biotechnological Information (NCBI) database. A list of these uniESTs, sorted from most to least likelihood based on the expected value from the blast search in public databases, was used to create tools for each of the three studies. First, I described sixty-one genes encoding products known to be important in pesticide metabolism and in endocrinology, including cytochrome P450s, glutathione-S-transferases, acetylcholinesterase homologs, neuropetides and neurohormones. Findings on arachnid specific esterases and neuropetides, and possible benefits to pest management programs, were discussed. Next, I inferred divergence time for Acari and the point of divergence of two lineages within anactinotrichid mites, Ixodes scapularis and Phytoseiulus persimilis. I used expresses sequence tags from the predatory mite P. persimilis to pull out 74 orthologous amino acid sequences of invertebrates species: nine insect species, Daphnia pulex, Ixodes scapularis, and Caenorhabditis elegans. I estimated a similar origin for Chelicerata (578.1 ± 38.2 - 482.2 ± 7.2 Mya) as in other recent studies. However, divergence dating using amino acid sequences suggested a Devonian origin of anactinotrichid mites (487.6 ± 32.2 - 410.1 ± 6.1 Mya) based on four reference dates (two fossil records and two molecular clocks) and four amino acid substitution methods; this estimate is much earlier that those in the current literature. This discrepancy of divergence times may be due to the use of a global clock. Finally, I developed molecular markers from the EST dataset to examine inheritance in the haplodiploid system in P. persimilis. Biparental contribution of chromosomes is required among the predatory mites but the paternal chromosome set seems to be eliminated or loss (Paternal genome loss, PGL) in male offspring. However, genetic studies in other two phytoseiid species were suggested diploid males with PGL only in the germ cells. In the present study, haploid adult males of P. persimilis have been observed using five independent EST-derived markers. Single mites derived from inter-population crosses were genotyped after whole genome amplification. The parahaploid genetic system in P. persimilis is supported by this study, in which both sexes arise from fertilized eggs but the paternal chromosome set is subsequently lost in males.
Keywords: Expressed sequence tags; Phytoseiulus persimilis; Mite divergence time; Parahaploidy; Entomology (0353)